RECONSIDERATION OF KANGRA MINIATURE PAINTING FROM THE DESIGN PERSPECTIVE - Raha, Prosenjit (ShodhKosh: Journal of Visual and Performing Arts, 2023)
The style of Kangra miniature paintings never ignores the necessity of intricate craftsmanship. The craft qualities in Kangra miniature painting are bringing new opportunities to be revived. Every intricate decorative pattern or motif of this style is a piece of innovative design and required to be analyzed and evaluated from a modern perspective. It has the potential to develop a language of modern Indian decorative design. Exploring the future possibilities of the crafts in Kangra miniature paintings is the prime objective of this research article. To understand design potentials practically in this style, the author had been trained under the traditional Kangra artists for two months in Kangra. The author has also observed the collaborative activities of NIFT Kangra with them. The fieldwork also included visits to the historical Kangra fort and temples where the original remains of traditional Kangra-style architectures, exteriors, and interior designs exist even today. The paper argues, design elements in such traditional art carry the idioms of the cultural identity of a community. The patterns and motifs of the Kangra style carry the Indian idioms of design. It requires more attention from the perspective of Cultural Sustainability.